The Effect of Baamboozle-Assisted Digital Learning Media on Students’ Learning Motivation and Critical Thinking Skills in Natural and Social Sciences Learning - Laely Rizki Maulida; Tri Joko Raharjo; Sri Wardani (Proceedings of International Conference on Science, Education, and Technology, 2026)
The integration of digital learning media in elementary schools requires the use of media that are not only engaging but also capable of supporting students’ learning motivation and critical thinking skills. Baamboozle is a game-based learning platform that provides quiz activities, scoring, simple competition, feedback, and classroom interaction, making it relevant for use in Natural and Social Sciences learning. This study aimed to examine the effect of Baamboozle-assisted digital learning media on elementary school students’ learning motivation and critical thinking skills. This research employed a quantitative approach using a quasi-experimental posttest-only nonequivalent control group design. The participants consisted of 53 third-grade elementary school students who were divided into a Baamboozle group and a conventional learning group. Data were collected using a learning motivation questionnaire and a critical thinking skills test, both of which had been tested for validity and reliability. The data were analyzed using MANOVA (Multivariate Analysis of Variance). The results showed that Baamboozle-assisted digital learning media had a significant simultaneous effect on students’ learning motivation and critical thinking skills. The between-subjects test also indicated significant differences between the Baamboozle group and the conventional group in both learning motivation and critical thinking skills, with the Baamboozle group obtaining higher mean scores on both variables. These findings suggest that Baamboozle can be used as a digital learning medium that supports both the affective and cognitive aspects of students in elementary school Natural and Social Sciences learning.